2017
DOI: 10.1007/s11920-017-0854-y
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Trauma-Related Psychopathology: a Critical Review of Neuroimaging Literature (2014–2017)

Abstract: Purpose of Review Sex differences in the epidemiology and clinical presentation of trauma-related psychopathology have long been documented. Multiple underlying mechanisms have been examined, both psychosocial and biological. Among the most promising biological mechanisms are neural substrates of trauma-related psychopathology that have been uncovered in recent years. Recent Findings Neuroimaging studies of sex-related heterogeneity published over the past 3 years (2014–2017) demonstrate an interaction betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 115 publications
(120 reference statements)
4
30
0
Order By: Relevance
“…Multiple studies indeed show that childhood adversities, ranging from low birth weight or social status to severe maltreatment or abuse, are associated with chronically-elevated cortisol levels ( Sheridan et al, 2013 ; Frodl and O'Keane, 2013 ; Engert et al, 2010 ; Dahmen et al, 2018 ; Bremner, 2005 ), but lower hippocampal volumes ( Dahmen et al, 2018 ; Samplin et al, 2013 ; Frodl et al, 2017 ; Everaerd et al, 2012 ; Calem et al, 2017 ). While there seem to be no sex differences in MDD effects on hippocampal volumes, effects of childhood adversities are consistently stronger in males ( Samplin et al, 2013 ; Everaerd et al, 2012 ; Calem et al, 2017 ; Helpman et al, 2017 ). Following the idea that smaller hippocampal volumes are not so much a result of chronically elevated cortisol levels, but represent a vulnerability factor for HPA-axis dysregulation due to severe stress, the fact that pre-adolescent girls have larger hippocampi and a larger cortisol response than boys may contribute to this finding ( Whittle et al, 2011 ).…”
Section: Neuroimaging Studies On the Effects Of Sex And Stress Hormonmentioning
confidence: 83%
“…Multiple studies indeed show that childhood adversities, ranging from low birth weight or social status to severe maltreatment or abuse, are associated with chronically-elevated cortisol levels ( Sheridan et al, 2013 ; Frodl and O'Keane, 2013 ; Engert et al, 2010 ; Dahmen et al, 2018 ; Bremner, 2005 ), but lower hippocampal volumes ( Dahmen et al, 2018 ; Samplin et al, 2013 ; Frodl et al, 2017 ; Everaerd et al, 2012 ; Calem et al, 2017 ). While there seem to be no sex differences in MDD effects on hippocampal volumes, effects of childhood adversities are consistently stronger in males ( Samplin et al, 2013 ; Everaerd et al, 2012 ; Calem et al, 2017 ; Helpman et al, 2017 ). Following the idea that smaller hippocampal volumes are not so much a result of chronically elevated cortisol levels, but represent a vulnerability factor for HPA-axis dysregulation due to severe stress, the fact that pre-adolescent girls have larger hippocampi and a larger cortisol response than boys may contribute to this finding ( Whittle et al, 2011 ).…”
Section: Neuroimaging Studies On the Effects Of Sex And Stress Hormonmentioning
confidence: 83%
“…Additionally, there is increasing evidence for a gender-specific pattern of the described structural and functional changes: While male individuals largely present PFC, amygdala and hippocampus gray matter reductions following traumatic exposure, females often present with amygdala hyperactivity. This might not only explain the heterogeneity of study results, but also suggest far-reaching implications for the selection of adequate therapeutic measures (74).…”
Section: Discussionmentioning
confidence: 99%
“…In a small study employing an acute laboratory stressor, men showed increased activation in the prefrontal cortex while women displayed elevated activity in limbic regions, including the ventral striatum and cingulate (Wang et al, 2007). In terms of structural changes due to stress, childhood trauma may impact the hippocampal volume of males more than females (reviewed in Tiwari and Gonzalez, 2018) and may enlarge amygdala and decrease connectivity of salience hubs such as the dACC in females more than males (Helpman et al, 2017). Animal studies have delineated some of the mechanisms of sex differences.…”
Section: Biological Impact Of Chronic Stress On the Brain Peripherymentioning
confidence: 99%